Essentials of glaucoma surgery - Kahook, Malik Y. (SLACK Inc., 2012)
"Essentials of Glaucoma Surgery provides a window into glaucoma surgical procedures with rapid insight and ready-to-reference information from more than 50 experienced surgeons in the profession. This resource uses a real world approach to explain surgical glaucoma, allowing the information to be quickly digested and put to use by the reader. Essentials of Glaucoma Surgery is led by Dr. Malik Y. Kahook and uses concise and straightforward text to clearly explain surgical procedures, along with pearls of practice to augment the chapters and provide advice from the experts, therefore preparing the reader for the operating room. This comprehensive handbook offers explanations of surgical instruments, expert FDA information related to current regulation of surgical devices in the United States, and an appendix of surgical dictations. Essentials of Glaucoma Surgery also includes sections that uniquely add historical context, as well as sections with information on the regulatory environment as it relates to devices used for the surgical management of glaucoma. Additionally, a section is included that offers perspectives from renowned experts on glaucoma surgery from where it began to where the future will go. With its real-world approach, user-friendly format, expert advice, and unique point of view, practicing ophthalmologists, residents, fellows, and medical students will benefit from Essentials of Glaucoma Surgery"--Provided by publisher